Masalah Penentuan Lokasi Dan Rute Pencemaran Dengan Mempertimbangkan Jarak Minimum Fasilitas Ke Wilayah Perumahan Dan Rute Majemuk - Andi Muhammad Fiqri Achmad; Andi Velahyati Baharuddin (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
The minimum distance of the new facility from the residential area is as far as 2 kilometers. Regulations are made to prevent pollution that can pollute residential areas. This study discusses the problem of determining the location of new facilities and determining the route of pollution vehicles by considering the minimum distance of the facility to the residential area of the compound route. The purpose of this study is to develop a mathematical model for the problem of determining the location of facilities and vehicle routes that considers the minimum distance of the facility to residential housing and compound routes. This study develops a mathematical model in the form of Mixed Integer Quadratic Programming (MIQP). The trial was conducted with 2 scenarios, namely 2 and 3 facility candidates, and from 7 to 13 customers. The trial scenario was carried out by changing the minimum distance from the facility candidate to the residential area, so that each scenario had 21 data processing times. From the results of data processing for the 2 facility candidates obtained, it can be seen that between the number of customers 7 to 13 there is no noticeable difference, and it still tends to look the same. Likewise with 3 facility candidates who do not show too big differences or even tend to be the same. The results obtained for 2 facility candidates with a minimum distance of 200 were 21,385.3, and the results for 3 facility candidates with a minimum distance of 200 were 21,237.3.